Inhibition of gap junctions sensitizes primary glioblastoma cells for temozolomide - Potthoff, Anna Laura; Heiland, Dieter Henrik; Evert, Bernd O.; Almeida, Filipe Rodrigues; Behringer, Simon P.; Dolf, Andreas; Güresir, Ági; Güresir, Erdem; Joseph, Kevin; Pietsch, Torsten; Schuss, Patrick; Herrlinger, Ulrich; et al. (Cancers, 2019)
Gap junctions have recently been shown to interconnect glioblastoma cells to a multicellular syncytial network, thereby allowing intercellular communication over long distances as well as enabling glioblastoma cells to form routes for brain microinvasion. Against this backdrop gap junction-targeted therapies might provide for an essential contribution to isolate cancer cells within the brain, thus increasing the tumor cells’ vulnerability to the standard chemotherapeutic agent temozolomide. By utilizing INI-0602—a novel gap junction inhibitor optimized for crossing the blood brain barrier—in an oncological setting, the present study was aimed at evaluating the potential of gap junction-targeted therapy on primary human glioblastoma cell populations. Pharmacological inhibition of gap junctions profoundly sensitized primary glioblastoma cells to temozolomide-mediated cell death. On the molecular level, gap junction inhibition was associated with elevated activity of the JNK signaling pathway. With the use of a novel gap junction inhibitor capable of crossing the blood–brain barrier—thus constituting an auspicious drug for clinical applicability—these results may constitute a promising new therapeutic strategy in the field of current translational glioblastoma research.
CRIS-Team Scopus Importer:2024-03-07
Keywords: C-Jun; Cell death; Gap junctions; Glioblastoma; INI-0602